2007
DOI: 10.1021/nl071521o
|View full text |Cite
|
Sign up to set email alerts
|

Active Nanodiamond Hydrogels for Chemotherapeutic Delivery

Abstract: Nanodiamond materials can serve as highly versatile platforms for the controlled functionalization and delivery of a wide spectrum of therapeutic elements. In this work, doxorubicin hydrochloride (DOX), an apoptosis-inducing drug widely used in chemotherapy, was successfully applied toward the functionalization of nanodiamond materials (NDs, 2-8 nm) and introduced toward murine macrophages as well as human colorectal carcinoma cells with preserved efficacy. The adsorption of DOX onto the NDs and its reversible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
418
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 531 publications
(439 citation statements)
references
References 74 publications
6
418
0
10
Order By: Relevance
“…115 For example, a nanodiamonddoxorubicin conjugate was found to induce apoptosis in various cancer cell lines and suppress tumor growth in mouse models of liver and mammary cancer. 116,117 By loading this drug on the nanodiamonds, its side effects were diminished and its release was delayed. In one very recent example, a multifunctional platform based on nanodiamonds was constructed, which could be used for selective targeting, imaging and therapy.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…115 For example, a nanodiamonddoxorubicin conjugate was found to induce apoptosis in various cancer cell lines and suppress tumor growth in mouse models of liver and mammary cancer. 116,117 By loading this drug on the nanodiamonds, its side effects were diminished and its release was delayed. In one very recent example, a multifunctional platform based on nanodiamonds was constructed, which could be used for selective targeting, imaging and therapy.…”
Section: Figurementioning
confidence: 99%
“…132,133 Through comprehensive bioassays, it was confirmed that nanodiamonds do not induce inflammation or the production of tumor necrosis factor alpha or inducible nitric oxide synthase in cells after incubation. 117 Furthermore, by taking advantage of the intrinsic fluorescence of nanodiamonds, their biodistribution and biocompatibility were evaluated using a C. elegans and a mouse model. It was concluded that nanodiamonds with various surface modifications were nontoxic and highly biocompatible.…”
Section: Toxicity Of Spherical Nanocarbon Materials-are Spherical Nanmentioning
confidence: 99%
“…133,134 Despite this consideration, assays that utilize MTT or similar cell vitality stain reagents for measuring cellular proliferation and growth continue to be extensively applied for the routine assessment of true chemotherapeutic cytotoxic anti-neoplastic potency. 7,26,30,[135][136][137][138][139] Fourth, cytotoxic anti-neoplastic potency could have been delineated in vivo against human neoplastic xenographs in animal hosts as a model for human neoplasia where the efficacy of a covalent immunochemotherapeutic frequently tends to be higher than in ex vivo tissue culture based models utilizing the same identical cancer cell type. 39,42,140 The enhanced levels of covalent immunochemotherapeutic potency measured in vivo is presumed in part to be dependent upon contributions from endogenous immune responses that include antibody-dependent cell cytotoxicity (ADCC) phenomenon in concert with complemented-mediated cytolysis initiated by the formation of antigen-immunoglobulin complexes on the exterior surface membrane of ''targeted'' neoplastic cells.…”
Section: Cytotoxic Anti-neoplastic Potencymentioning
confidence: 99%
“…ND particles, which are capable of mediating improved efficacy and safety by forming complexes around the active agent while preserving its innate functionality (20)(21)(22)(23)(24)(25)(26)(27). ND safety and biocompatibility have been clearly demonstrated in numerous applications ranging from oncology to wound healing (28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Significancementioning
confidence: 99%